Integrating XR for Live Broadcasting Workflows: An Industry Perspective - Dunphy, Bryan; Hynes, Eoghan; Keighrey, Conor; Dinan, Grace; Young, Gareth William; O’Fearghail, Colm; Hospital, Marie; Murray, Niall (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences Workshops, 2025)
This paper presents the results of an expert evaluation of how extended-reality (XR) head-mounted displays (HMD) may be integrated into live broadcasting workflows. To date, the adoption of HMD in live broadcasting remains limited despite the growing use of XR within virtual production. As part of the International Broadcasting Convention (IBC) 2024, industry professionals engaged with a technical XR demo that showcased a virtual control room and virtual studio. The application was experienced with the Quest 3 HMD. After the demonstrations, broadcast professionals provided feedback with respect to opportunities for XR within the control as part of live broadcasting workflows. Analysis of the results showed interest in XR solutions being integrated with existing progressive and accepted systems. The industry professionals highlighted potential cost savings via improved collaboration and efficiency. They also highlighted concerns in terms of potential technical limitations and the impact on adoption management. Interest levels and sentiment suggest that such positive XR experiences should lead to increased adoption. Further exploration with respect to XR’s role in broadcasting with respect to scalability and long-term impact.